Comparison between the automated reagin test and reagin screen test methods of VDRL screening tests for syphilis in use in a routine laboratory. Issue 7 (July 1977) - Simon, R D; Peacock, A M
Abstract : A comparison is made between the automated reagin test (ART) using Technicon AutoAnalyzer equipment and the reagin screen test (RST) introduced by Lederle using a new antigen formulation. Treponemal haemagglutination tests (TPHA) were done simultaneously as second screen tests. The absorbed fluorescent treponemal antibody test (FTA-ABS) was used in all seropositive cases. Altogether 1154 sera were tested; 1028 were negative with all tests, 66 were positive with all tests, 42 were positive with TPHA and negative with ART and RST, and 16 were positive with TPHA and RST and negative with ART. It was concluded that the use of the RST and TPHA together would be the more sensitive screen test.